2019
DOI: 10.1128/mbio.02846-18
|View full text |Cite
|
Sign up to set email alerts
|

Introducing THOR, a Model Microbiome for Genetic Dissection of Community Behavior

Abstract: The quest to manipulate microbiomes has intensified, but many microbial communities have proven to be recalcitrant to sustained change. Developing model communities amenable to genetic dissection will underpin successful strategies for shaping microbiomes by advancing an understanding of community interactions. We developed a model community with representatives from three dominant rhizosphere taxa, the Firmicutes, Proteobacteria, and Bacteroidetes. We chose Bacillus cereus as a model rhizosphere firmicute and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 61 publications
2
61
0
Order By: Relevance
“…It is possible that difficult-to-cultivate species may only emerge in the context of a community, requiring interactions with other members and precluding their growth as axenic strains without more biochemical information. Species that co-isolate together is a phenomenon that has been seen previously (Lozano et al, 2019). These "hitchhikers" have been used to build consortia that have a high probability of containing interacting organisms.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is possible that difficult-to-cultivate species may only emerge in the context of a community, requiring interactions with other members and precluding their growth as axenic strains without more biochemical information. Species that co-isolate together is a phenomenon that has been seen previously (Lozano et al, 2019). These "hitchhikers" have been used to build consortia that have a high probability of containing interacting organisms.…”
Section: Discussionmentioning
confidence: 96%
“…One approach to investigate the high diversity and complexity of the soil microbiome is to develop reduced complexity model consortia. Ideally, a model consortium would have a tractable and reproducible number of species that are amenable to genetic manipulation and that would enable experimental analysis of population dynamics and specific metabolic and signaling interactions between members (Lozano et al, 2019;Zengler et al, 2019). Ultimately, knowledge gained by analysis of these reduced complexity communities should help to reveal details of metabolic and interspecies interactions that may take place in the native soil community.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of interactions within synthetic communities based on plant microbiomes found widespread inhibitory interactions and led to the discovery of novel antimicrobial compounds. For example, the THOR model rhizosphere microbiome, presented by Lozano and coworkers ( 16 ), was found to contain Pseudomonas koreensis , the producer of koreenceines A to C. These molecules had inhibitory activity against another member, Flavobacterium johnsoniae . In another example, in a phyllosphere model presented by Helfrich and coworkers ( 15 ), binary interaction networks were created and bioactivity-guided fractionation led to the discovery of multiple novel molecules produced by Brevibacillus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized metabolites produced by microbes, including molecules with antibacterial, antifungal, and siderophore activities, have been hypothesized to play a role in shaping plant microbiomes. For example, specialized metabolites may influence interactions between members of plant microbiomes ( 15 17 ) and may be a mechanism of protection from pathogen invasion ( 7 , 17 ). Thus, there is interest in leveraging specialized metabolism by plant-associated microbes in agriculture and for discovery of novel compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation